Collagen reorganization in cartilage under strain probed by polarization sensitive second harmonic generation microscopy. Issue 150 (16th January 2019) - Mansfield, Jessica C.; Mandalia, Vipul; Toms, Andrew; Winlove, C. Peter; Brasselet, Sophie
Abstract : Type II collagen fibril diameters in cartilage are beneath the diffraction limit of optical microscopy, which makes the assessment of collagen organization very challenging. In this work we use polarization sensitive second harmonic generation (P-SHG) imaging to map collagen organization in articular cartilage, addressing in particular its behaviour under strain and changes which occur in osteoarthritis. P-SHG yields two parameters, molecular order and orientation, which provide measures of the degree of organization both at the molecular scale (below the diffraction limit) and above a few hundred nanometres (at the image pixel size). P-SHG clearly demonstrates the zonal collagen architecture and reveals differences in the structure of the fibrils around chondrocytes. P-SHG also reveals sub-micron scale fibril re-organization in cartilage strips exposed to tensile loading, with an increase in local organization in the superficial zone which weakly correlates with tensile modulus. Finally, P-SHG is used to investigate osteoarthritic cartilage from total knee replacement surgery, and reveals widespread heterogeneity across samples both microscale fibril orientations and their sub-micron organization. By addressing collagen fibril structure on scales intermediate between conventional light and electron microscopy, this study provides new insights into collagen micromechanics and mechanisms of degradation.